The Interaction of Zinc Oxide/Green Tea Extract Complex Nanoparticles and its Effect on Monosodium Glutamate Toxicity in Liver of Rats - Al-Salmi, Fawziah A.; Hamza, Reham Z.; El-Shenawy, Nahla S. (Current Pharmaceutical Biotechnology, 2019)
Background: Zinc oxide nanoparticles (ZnO NPs) are increasingly utilized in both industrial and medical applications. Therefore, the study was aimed to investigate the effect of green nanoparticle complex (green tea extract/zinc oxide nanoparticles complex, GTE/ZnO NPs) on oxidative stress induced by monosodium glutamate (MSG) on the liver of rats. Methods: Wistar male rats (n=64) weighing between 200-250 g were divided randomly into eight groups: control group was given physiological saline (1 mg/kg), two groups were treated with two different doses of MSG (MSG-LD, MSG-HD; 6 and 17.5 mg/Kg, respectively), GTE was given 1 mg/mL, 5th group was treated with ZnO NPs and 6th group was treated with GTE/ZnO NPs complex while, 7th and 8th groups were treated with MSG-LD + GTE/ZnO NPs complex and MSG-HD + GTE/ZnO NPs complex, respectively. All substances were given orally for 30 consecutive days. At the end of the study, the liver was homogenized for measurement of the oxidative stress status and anti-inflammatory biomarkers as well as histological and transmission alternations. Results: Results showed that the antioxidant enzymes activity and glutathione level were significantly decreased in MSG groups than control in a dose-dependent manner. Conversely, the malondialdehyde and inflammatory cytokines levels were significantly increased in MSG groups than the control group. The liver indicated no evidence of alteration in oxidative status, anti-inflammatory and morphological parameters in GTE, ZnO NPs and GTE/ZnO NPs complex groups. Conclusion: In conclusion, MSG at both doses caused oxidative stress and inflammation on liver after 28 days of exposure that supported histological analysis and transmission view of hepatic parenchyma. GTE/ZnO NPs act as partial hepato-protective against MSG.
Keywords: Anti-inflammatory